2021
DOI: 10.3390/jcm10214992
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes in Fibromyalgia Suggest the Role of the Immune-Inflammatory Response and Central Sensitization

Abstract: Fibromyalgia (FM) has been explained as a result of gene-environment interactions. The present study aims to verify DNA methylation differences in eleven candidate genome regions previously associated to FM, evaluating DNA methylation patterns as potential disease biomarkers. DNA methylation was analyzed through bisulfite sequencing, comparing 42 FM women and their 42 healthy sisters. The associations between the level of methylation in these regions were further explored through a network analysis. Lastly, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Of these, the study investigating 112 regions within 100 genes (including NR3C1 ) found no group differences in methylation (46). The larger follow-up study by the same group, which included all pilot cases, investigated 12 regions within 11 genes (including NR3C1 ) and found one site within GCSAML , the gene encoding the germinal center–associated signaling and motility-like protein, to be hypomethylated in women with fibromyalgia compared with controls (47).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the study investigating 112 regions within 100 genes (including NR3C1 ) found no group differences in methylation (46). The larger follow-up study by the same group, which included all pilot cases, investigated 12 regions within 11 genes (including NR3C1 ) and found one site within GCSAML , the gene encoding the germinal center–associated signaling and motility-like protein, to be hypomethylated in women with fibromyalgia compared with controls (47).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroplastic changes, including long-term potentiation (LTP) and long-term depression (LTD) ( Kourosh-Arami et al, 2021 ), refer to the ability of the brain to reshape itself by generating new neural connections. Because of this adaptability, FMS causes an overactive brain pain processing system and generalized widespread pain ( Gerra et al, 2021 ; Jayakar et al, 2021 ; Mezhov et al, 2021 ). Neuroplastic changes are associated with brain-derived neurotrophic factor (BDNF), which affects neuronal growth and synaptic connectivity.…”
Section: Mechanisms Of Tdcs For Fibromyalgia Syndromementioning
confidence: 99%
“…Estes, por sua vez, podem modular a função do genoma e o fenótipo por meio de modificações covalentes de histonas, metilação do DNA ou RNAs não codificadores, sem que a sequência do DNA seja alterada (Low & Schweinhardt, 2012;Szyf & Bick 2013). Alguns estudos (em grande parte estudos piloto ou com pequeno número amostral) foram conduzidos com pacientes com FM e evidências sugerem uma prevalência da influência de padrões (hipo ou hiper) de metilação do DNA nesse grupo, em genes implicados em vias reparo de DNA, processos relacionados ao sistema imunológico, metabolismo relacionado a lipídios, transporte de membrana, sensibilização central, depressão, diferenciação neuronal, desenvolvimento do sistema esquelético e compactação da cromatina (Menzies et al, 2013;Ciampi de Andrade et al, 2017;Gerra et al, 2020;Gerra et al, 2021). Em um estudo com um pequeno grupo misto, composto por pacientes com FM e síndrome da fadiga crônica, resultados preliminares demonstraram que nesse grupo a metilação do DNA do BDNF foi menor em comparação aos indivíduos do grupo controle e que essa metilação é mediada pelo polimorfismo BDNF Val66Met, sugerindo que sua influência na expressão do BDNF possa se dar através desse mecanismo epigenético (Polli et al, 2020).…”
Section: Conclusãounclassified